Photoelectrochemical ruler: measurement at the micron scale. - Fietkau, N; del Campo, J; Mas, R; Muñoz, F; Compton, R (2007)
A new approach to the measurement of objects with dimensions in the micron scale is proposed exploiting the spatial sensitivity of electrochemical measurements.